The role of chemical fertilizer reduction and different microbial inoculants on yield increase in lettuce cultivation - Nurgul Kitir Sen; Ayhan Kocaman; Özlem Ete Aydemir (BMC Plant Biology)
Abstract The use of probiotics to reduce the use of chemical fertilizers in agriculture has proven to be a promising area of research, especially as the agricultural sector searches for sustainable alternatives to synthetic agents. However, there are few studies integrating probiotics into agricultural practices, especially in lettuce cultivation, to minimize the use of chemical fertilizers. Most previous research has focused on the effects of plant growth-promoting rhizobacteria (PGPR) and microalgae on yield, with little consideration of the combined effects of different microorganisms under the same soil and growing conditions. In this study, the effects of microbial biostimulants on the efficiency of fertilizer use in lettuce (Lactuca sativa L.) cultivation were investigated, reducing the use of chemical fertilizers by 25%. The trial was conducted as a randomized block trial in a high tunnel greenhouse and comprised eight treatments: a negative control (T0, no chemical fertilizers or microorganisms), a positive control (T1, 500 kg ha−1 NPK fertilizer) and treatments with single biostimulants — microalgae (Chlorella vulgaris, T2), plant probiotic microorganisms (PPMs, Lactobacillus spp, Rhodopseudomonas palustris, Saccharomyces cerevisiae, T3), and PGPRs (Bacillus subtilis, Bacillus megaterium, Bacillus amyloliquefaciens, T4). Further treatments combined reduced fertilizer (375 kg ha−1 NPK) with microalgae (T5), PPMs (T6) and PGPRs (T7). The results showed that T6 (PPMs + reduced fertilizer) achieved the highest plant weight (364 g) and leaf length (43.8 cm), with increases of 152% and 128%, respectively, compared to the control (T0). Chlorophyll content improved significantly in T5 (27.5%) and T7 (29.4%) compared to T0. Biomass production was 78% higher in T6 than in T1, while T5 and T7 showed a moderate increase in biomass of 42% and 47%, respectively. Cluster analysis identified T6 as the most effective treatment, outperforming T1 in growth parameters. These results demonstrate the potential of microbial biostimulants, especially in combination with reduced chemical fertilizers, to increase plant growth, biomass production and fertilizer efficiency. The study underlines their role in promoting sustainable agriculture and provides a basis for future research under different soil and environmental conditions.